Site-directed mutagenesis of an HLA-A3 gene identifies amino acid 152 as crucial for major-histocompatibility-complex-restricted and alloreactive cytotoxic-T-lymphocyte recognition. - Cowan, E P (1987)
Major histocompatibility complex-restricted and alloreactive cytotoxic T lymphocytes (CTL) can discriminate between the HLA-A3.1 and HLA-A3.2 antigens. HLA-A3.1 and the rare variant HLA-A3.2 have been shown to differ by two amino acids in the alpha 2 domain at positions 152 (A3.1, glutamic acid; A3.2, valine) and 156 (A3.1, leucine; A3.2, glutamine). To determine the structural basis for the ability of CTL to differentiate A3.1 from A3.2, two site-directed mutants of the HLA-A3.2 gene were produced, 152A3.1-156A3.2 and 152A3.2-156A3.1, that have the indicated codons for positions 152 and 156. These mutated HLA-A3 genes, as well as the nonmutated HLA-A3.1 and HLA-A3.2 genes, were then transfected into the murine cell line P815-HTR and used as targets for human CTL. Influenza virus-specific HLA-A3.1-restricted CTL lysed virus-infected P815 cells transformed with the HLA-A3.1 and 152A3.1-156A3.2 genes, but not P815 cells transformed with the HLA-A3.2 and 152A3.2-156A3.1 genes. HLA-A3.2-allospecific CTL lysed the P815 cells transformed with the HLA-A3.2 and 152A3.2-156A3.1 genes but did not lyse P815 cells transformed with the HLA-A3.1 or 152A3.1-156A3.2 genes. Thus, a single amino acid change at position 152, substituting valine for glutamic acid and thereby introducing a charge difference, produces major structural changes in the epitopes recognized by major histocompatibility complex-restricted and alloreactive CTL.